PENINGKATAN PERINGKAT AKREDITASI MENGGUNAKAN HOUSE OF QUALITY PADA SEKOLAH TINGGI DI KOPERTIS WILAYAH IV - Nustin Merdiana Dewantari; Dana Santoso Saroso (Operations Excellence: Journal of Applied Industrial Engineering, 2017)
The competitiveness among the university is getting sharper, not just among the public university but also the private university. High Schools in Kopertis IV (West Java and Banten) need to assess and improve the rank of accreditation of higher education so that the strength and confidence level of institutional markets increases.  The rank of accreditation is A (Excellence), B (Good), C (Enough). With the availability of accreditation available there is C, no doubt the power of sale and quality of the university has been described. Establishment of institution accreditation is one of the guides customers see when choosing a colleague. Accreditation is a quality assurance made by the institution so that all efforts undertaken are within the environment set by the National Accreditation Higher Learning Institute. Submission of quality function deployment at house of quality phase 1 found 23 technical responses to answer 28 cases of weaknesses that need to be improved in the quality of the assessment results that have been done.  With using HOQ, High School in Kopertis IV region can find out the priority items that need to be improved the promotion rank of accreditation.